The Effect of NaCl Concentration and Incubation Time on Oxalate and Total Acid in Fermented Cabbage using Various Microorganisms - Arie Srihardyastuti; Sasangka Prasetyawan; Radhinal Zikri Firdaus; Fidelia Berenice Prayugo; Yolanda Kresmonia; Tinok Dwi Ananda; Alfi Salamah (Chemistry Department, The University of Brawijaya, 2021)
As the highest agrocultural product, cabbage (Brassica oleracea var. capitata) remain consider as perishable vegetable and also known to contain an antinutritional compound, called oxalate. The oxalate salts is non-soluble compound in water, and thus settle on human kidney. The preservation and improvement of the nutritional aspect of cabbage can be achieved by fermentation through the enzyme production. Therefore, we study the effect of salt addition and incubation time, as the two important factor in commonly cabbage-based fermentation, combined with someoxalate-degrading-bacteria, which wasL. plantarum, L. plantarum – S. cerevisiae, and A. aceti – S. cerevisiae on the oxalate and total acid level in cabbage fermentation. The fermentation was conducted in submerged system at room temperature (25 – 27 °C) with the NaCl concentration addition ranging from 0 – 5% until 10 days. Those condition was carried out for the three types of the tested cultures. The oxalate and total acid level was measured using the permanganometric and acid base titration, respectively. The results indicated that L. plantarum-induced fermentation combined with 3% NaCl during 10 days gave the lowest oxalate level in the fermented cabbage biomass,which was 0.005 mg/100 g FW. Moreover, these single-cultured fermentation was able to produce the highest total acid level in the brine solution, 1.270% at the 8 days of fermentation. This fermentation serves as an alternative method to improve cabbage consumption.